(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The extent of the risk of falling rises with ageing, and the number of falls and accidents that occur strongly contributes to admission to a nursing home. Fall is mostly caused due to lack of balance and also affect the quality of life, so the various Physiotherapy approaches are available for prevention and treatment of fall but very few studies utilized computerized balance board training program to improve the balance, hence need for the study is to find out the efficacy of balance board training & to enhancing balance and gait as well as the significance of these training on static and dynamic stability and quality of life in the geriatric population. Method: Total n=96 elderly people will be targeted who are about 60 years of age or older. Participants will be randomly separated into two groups (control or experimental group).The training session design for a 6 weeks and each session for a 20-30 minute. Outcome measures will be used to assess the static and dynamic stability and quality of life in the elder population group. Discussion: This clinical work seeks to equate the impact of traditional wobble board balance instruction in the elderly community and computer-based balance board preparation. To conclude, this work will help elderly people strengthen their static and dynamic equilibrium, and also increase their quality of life.